Methodological meaning of person in law category and determination problems of air law subject - Сопілко, Ірина Миколаївна; Гладка, Ірина Володимирівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2010)
In this article an author researches the question of comparative legal characteristics of persons in law andsubjects of jural relationships. Separate attention is devoted to the study of concept of air law field and air law subjects.